An interventional study with health education to modify the risk factors for the control of blood pressure among the newly diagnosed adult hypertensives, Andhra Pradesh - Ravi Sankar Deekala; Altaf Hussain R; Ravi Prabhu G (Public Health Review: International Journal of Public Health Research, 2018)
Background: India is developing rapidly, which is evidenced by its developmental indicators. The country is in transitional period between developing and developed nations. With the effect of globalization, the lifestyleof the people also changed rapidly from traditional way of living to western style of living, which is contributing to rapid changes in disease patterns. The incidence and prevalence of Non-communicable diseases is increasing when compared with communicable diseases, which are associated with changes in the life style. The prevalence of hypertension and its risk factors are increasing in India. The present study was done among the newly diagnosed adult hypertensive subjects to find out whether health educationfor modification in the diet and lifestyle factors will have any effect in the control of hypertension.Objective: To study the effect of health education intervention ondiet, lifestyle factors and thereby decrease in blood pressure levels among newly diagnosed adult hypertensive subjects.Methodology: A total of 60 newly diagnosed adult hypertensive subjects were selected randomly from a recent study done among the adults of both sex living in urban slum areas of Tirupati, Andhra Pradesh for this interventional study. Out of these, 30 subjects each were randomly allocated to the study and control groups. Results- In the study group, after health education intervention the proportion of hypertension decreased from 100% to 60% while in the controls, where health education was not given, it decreased from 100% to 90% only.Conclusion: There has been significant difference in the reduction of hypertension in the study group compared to control group. There has been reduction in all the risk factors studied after the intervention compared to the pre-intervention levels in the study group but however the differences were statistically significant with regard to extra salt intake, saturated fat intake and adequate fiber intake.